anti-Tricyclo[4.2.1.12,5]deca-3,7-diene-9,10-dione - Matthew P. Gidaly; Andria D. Harris; Maria del Rosario I. Amado-Sierra; Daniel S. Jones; Markus Etzkorn (Acta Crystallographica Section E, 2009)
The title compound, C10H8O2, is a precursor to an unusual bis-homoaromatic dication and to heterodiamantanes and other oxa-cage compounds. Two independent molecules, each of which is situated on a center of symmetry, comprise the unit cell. Both molecules are in nearly identical chair conformations.